The Influence of Cooking Class Center on Children's Science Skills at TK Negeri Pembina, Gorontalo City - Novita Ibrahim Hantulu; Pupung Puspa Ardini; Sri Rawanti (Indonesian Journal of Early Childhood Education Studies, 2025)
The purpose of this study is to determine the influence of the cooking class learning center on the science skills of children aged 4–5 years at TK Negeri Pembina, Kota Tengah District, Gorontalo City. This research employed a quantitative approach using a pre-experimental method with a one-group pre-test and post-test design. The study involved a sample of 17 children and revealed a difference in the average scores between the pre-test (16.41) and post-test (31.71). The hypothesis testing using linear regression analysis showed a significance value of 0.000, which is less than 0.05, indicating that the alternative hypothesis (Ha) is accepted. These results demonstrate that the use of the cooking class center has a significant effect on the science skills of children aged 4–5 years at TK Negeri Pembina, Kota Tengah District, Gorontalo City.